2022
DOI: 10.1093/braincomms/fcac278
|View full text |Cite
|
Sign up to set email alerts
|

Different depression: motivational anhedonia governs antidepressant efficacy in Huntington’s disease

Abstract: Depression is more common in neurodegenerative diseases such as Huntington’s disease than the general population. Antidepressant efficacy is well-established for depression within the general population: a recent meta-analysis showed serotonin norepinephrine reuptake inhibitors, tricyclic antidepressants and mirtazapine outperformed other antidepressants. Despite the severe morbidity, antidepressant choice in Huntington’s disease is based on class IV evidence. We used complementary approaches to determine trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 200 publications
0
5
0
1
Order By: Relevance
“…Another proposed mechanism by which tianeptine may improve symptoms of HD is by restoring neuronal calcium signaling via store-operated Ca++ channels ( Czeredys, 2020 ). While the underlying mechanism of tianeptine in preclinical HD models is not yet understood, several other antidepressants (e.g., SSRIs and bupropion) are already used in clinical settings ( McLauchlan et al, 2022 ), supporting the conclusion that tianeptine may be a viable treatment in HD patients. Tianeptine is considered safe and efficacious in another neurodegenerative disease, Parkinson’s Disease ( Agüera-Ortiz et al, 2021 ).…”
Section: Discussionmentioning
confidence: 97%
“…Another proposed mechanism by which tianeptine may improve symptoms of HD is by restoring neuronal calcium signaling via store-operated Ca++ channels ( Czeredys, 2020 ). While the underlying mechanism of tianeptine in preclinical HD models is not yet understood, several other antidepressants (e.g., SSRIs and bupropion) are already used in clinical settings ( McLauchlan et al, 2022 ), supporting the conclusion that tianeptine may be a viable treatment in HD patients. Tianeptine is considered safe and efficacious in another neurodegenerative disease, Parkinson’s Disease ( Agüera-Ortiz et al, 2021 ).…”
Section: Discussionmentioning
confidence: 97%
“…A previous study reported that sadness and depressed mood were early symptoms of HD (Paoli et al, 2017). Depression in HD is associated with motivational anhedonia, and it has been reported in approximately half of gene-positive HD family members (Gubert et al, 2020; Mclauchlan et al, 2022; Paulsen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Participants completed a phonemic verbal fluency task as a measure of cognitive impairment–a standard assessment of cognition in HD ( Landwehrmeyer et al, 2016 ). This study was part of a wider research project into the cognitive basis of psychopathology in HD ( McLauchlan, 2018 ), the total battery of 14 tasks also included tasks measuring motivation, learning, estimation and other cognitive processes hypothesised to contribute to apathy ( McLauchlan et al, 2019 ) and depression ( McLauchlan et al, 2022 ), although there is no overlap with the tasks and questionnaires presented in this work. The battery was administered in random order.…”
Section: Methodsmentioning
confidence: 99%